Deregulation of Market Stall Pharmaceutical Businesses: Supervisory Gaps and State Responsibility: Deregulasi Usaha Los Pasar Obat: Kesenjangan Pengawasan dan Tanggung Jawab Negara - Syafarudin, Heru (Mendapo: Journal of Administrative Law, 2026)
The Market Stall Pharmaceutical Business Policy under Minister of Health Regulation No. 11 of 2025 represents a deregulation measure that expands the retail distribution of over the counter medicines beyond formal pharmaceutical service facilities. While intended to enhance public access to medicines, particularly in underserved areas, this policy raises fundamental legal concerns regarding regulatory coherence, supervisory design, and the scope of state responsibility in safeguarding consumer safety. This study examines the policy from the perspective of health administrative law and consumer protection, emphasizing the precautionary principle, state responsibility, and state liability as normative benchmarks. Employing a doctrinal legal method with statutory, conceptual, and comparative approaches, the research also reviews supervisory models for over-the-counter medicines in selected Asian jurisdictions. The findings reveal three critical regulatory gaps: vertical inconsistency between deregulation norms and higher health legislation; horizontal fragmentation in inter agency supervision; and the absence of explicit state liability mechanisms in cases of consumer harm. These deficiencies extend beyond administrative technicalities and pose risks of maladministration, potentially undermining the constitutional right to health. The study argues that deregulation in the health sector cannot be construed as a reduction of state obligations. Rather, the state remains the ultimate guarantor of public safety and must ensure integrated, risk-based, and accountable supervision to prevent regulatory failure and to uphold consumer protection within the framework of the rule of law.